Graphic and Functional Algorithms of Sequence of Tenses in English Grammar for the Effective Education and Automated Systems of Text Synthesis and Editing - Lyudmila Kozlova; Nadejda Trubochkina (National Research University Higher School of Economics, 2015)
The article describes the optimal graphic language of presenting and studying English grammar using information technology. Among the studies on the use of graphics in teaching a foreign language, there are mostly descriptions of static objects. The authors propose to use a universal graphic language for describing processes. The authors suggest theoretical foundations of visualization of the English grammar rules using time-sequential conversion scale in the sequence of tenses transformation. The research question is the method of archiving knowledge of English grammar to simplify and speed up the memorization and to increase the volume of information memorized. To achieve this goal, the authors used a graphic algorithmization of the English grammar and visualization of grammar rules, as well as the comparative monitoring of the knowledge gained. As part of research, a series of experiments on the visualization of the rules of sequence of tenses were conducted in student groups. The research showed that a simple language of symbols facilitates and accelerates the memorization of English grammar. Systematic tabulation of grammar rules, where each verb tense gets its finished graphic image, becomes easy to understand and quick to memorize. The application of the presented approach is the following: effective linguistic education, local and global automatic synthesis system and text editing.